Suitability of The Implementation of Halal Tourism Principles at Sobo Kali Magelang Tourism: A Review of Fatwa DSN-MUI No. 108/DSN-MUI/X/2016 - Arief, Suyoto; Wicaksono, Muhammad Budi; Lahuri, Setiawan bin; Wibisono, Vina Fithriana; Hasbullah, Nurul Adilah Binti (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
Halal tourism in Indonesia is currently a phenomenon that has become a trend as a superior economic potential and state revenue. This is reinforced by the number of provinces that have implemented halal tourism programs with an increasing number of tourists from all over the world. However, the facts in the field are still a lot of halal tourism that has not met the quality standards in Islamic law. The purpose of this study is to determine appropriateness of the implementation of halal tourism at Sobo Kali Magelang Tourism in review of fatwa DSN-MUI No.108/DSN-MUI/X/2016. This research method is descriptive qualitative with a case study approach. Data collection techniques use observation, interniew, and documentation techniques. The results of this study indicate that the implementation of Sobokali halal tourism is in accordance with DSN-MUI Fatwa No. 180/DSN-MUI/X/2016 not yet maximized, which is caused by several aspects that result in not achieving the application of the principles of shariah as a whole. These aspects include, first, the absence of Sharia Financial Institution services in managing business results. Second, the standardization of food and beverages for Sobokali tourism has not yet received Halal Certification from DSN-MUI.